Dereverberation in noisy environments using reference signals and a maximum likelihood estimator - Braun, Sebastian; Habets, Emanuel (21st European Signal Processing Conference (EUSIPCO), 2013)
In speech communication systems the received microphone signals are commonly degraded by reverberation and ambient noise that can decrease the fidelity and intelligibility of a desired speaker. Reverberation can be modeled as nonstationary diffuse sound which is not directly observable. In this work, we derive an optimal signal-dependent informed spatial filter to reduce jointly reverberation and noise. In addition, we derive a novel maximum likelihood estimator for the power spectral density (PSD) of the diffuse sound, that makes use of a set of linearly independent reference signals. Experimental results show, that the proposed method provides an accurate estimate of the diffuse PSD, even with a small number of microphones. The proposed method outperforms two existing methods and is able to provide an optimal tradeoff between noise reduction and dereverberation